Rock sponges (lithistid Demospongiae) of the Northeast Atlantic seamounts, with description of ten new species - Carvalho, F. C.; Cárdenas, P.; Ríos, P.; Cristobo, J.; Rapp, H. T.; Xavier, J. R. (PeerJ, 2020)
Background: Lithistid demosponges, also known as rock sponges, are a polyphyletic group of sponges which are widely distributed. In the Northeast Atlantic (NEA), 17 species are known and the current knowledge on their distribution is mainly restricted to the Macaronesian islands. In the Mediterranean Sea, 14 species are recorded and generally found in marine caves. Methods: Lithistids were sampled in nine NEA seamounts during the scientific expeditions Seamount 1 (1987) and Seamount 2 (1993) organized by the MNHN of Paris. Collected specimens were identified through the analyses of external and internal morphological characters using light and scanning electron microscopy, and compared with material from various museum collections as well as literature records. Results: A total of 68 specimens were analysed and attributed to 17 species across two orders, seven families, and seven genera, representing new records of distribution. Ten of these species are new to science, viz. Neoschrammeniella inaequalis sp. nov., N. piserai sp. nov., N. pomponiae sp. nov., Discodermia arbor sp. nov., D. kellyae sp. nov., Macandrewia schusterae sp. nov., M. minima sp. nov., Exsuperantia levii sp. nov., Leiodermatium tuba sp. nov. and Siphonidium elongatus sp. nov., and are here described and illustrated. New bathymetric records were also found for D. ramifera, D. verrucosa and M. robusta. The Meteor seamount group has a higher